Ectopic Pregnancy - Khatun, Mst Hosna Ara (Journal of Dhaka National Medical College & Hospital, 2020)
Ectopic pregnancy remains a major gynecological emergency. Currently it remains a major problem in contemporary gynecological practice and continues to be an important cause of morbidity and mortality in women. Prevalence of ectopic pregnancy is 1-3% worldwide. The true current incidence of ectopic pregnancy is difficult to estimate because many patients are treated in an outpatient setting where events are not tracked and national surveillance data on ectopic pregnancy have not been update. Nearly all ectopic pregnancies are implanted within the fallopian. Ectopic implantation can also occur outside of the fallopian tube, within the cervix, ovary, abdomen, uterine cornua, and cesarean scars. The classic triad of symptoms, amenorrhea, abdominal pain, and abnormal bleeding varies greatly among individuals. Serial evaluation with transvaginal ultrasonography, or serum beta human chorionic gonadotrophin (hCG) level measurement or both often is required to confirm the diagnosis. The most common complication is rupture with internal bleeding which may lead to hypovolemic shock leads to death. So, a timely, early diagnosis can help patients obtain better pregnancy out-comes. The decision for surgical management or medical management of ectopic pregnancy should be guided by the initial clinical, laboratory and radiologic data as well as patient informed choice based on a discussion of the benefits and risks of each approach. J. Dhaka National Med. Coll. Hos. 2020; 26 (02): 36-40